Intellect and Concept - Gurpreet Rattan (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
The connections between theories of concepts and issues of knowledge and epistemic normativity are complex and controversial. According to the general, broadly Fregean, view that stands in the background of this paper, these connections are taken not only to exist, but also to be fundamental to issues about the individuation of concepts. This kind of view fleshed out should clarify the nature and role of epistemic norms, and of different kinds of epistemic norms, in concept individuation. This paper takes up an aspect of this general task and tries to make explicit the nature and role of intellectual norms, and to argue that extant paradigms for theorizing concepts fail because they fail to recognize the nature and individuative relevance of intellectual norms.